The league of beastly dreadfuls - Grant, Holly (Grant, Holly. League of beastly dreadfuls, 2015)
Anastasia, nearly eleven, is snatched from her elementary school and sent to live at a former insane asylum with two great-aunts she had never met after being told that her parents died in a tragic vacuum cleaner accident.